El liderazgo basado en la norma ISO 9001:2015 en las empresas procesadoras de café del cantón Piñas. - Pesantez Guerrero, Erika Anabel; Montoya Nagua, Maria Jose (Machala : Universidad Técnica de Machala, 2024)
This research work focuses on analyzing the leadership of coffee processing companies, under the ISO 9001:2015 standard. The main objective is to analyze the leadership of coffee processing companies in the Piñas canton, based on the ISO 9001:2015 standard, in order to contribute to the socioeconomic development of the region. For this, qualitative and quantitative research methods are used. Data collection is carried out through the application of interviews aimed at managers and surveys to employees, the population under study is the coffee processing companies in the province of El Oro canton Piñas, with a focus on two specific companies: Café Don Manuelito and Café Zambrano and data analysis tools are used, such as the SERVQUAL model, which allows evaluating key dimensions of leadership. The results show that managers only have knowledge about leadership and the application of the ISO 9001:2015 standard is intended. It is concluded that the leadership style applied is mostly democratic, thus promoting employee participation and commitment. It is also determined that the level of leadership in these companies is good, according to the perception of the collaborators. The research findings are expected to contribute to improving knowledge on the implementation of leadership according to ISO 9001:2015. The importance of training staff in leadership and teamwork is highlighted, as well as the development of function manuals to clarify roles within companies.
El presente trabajo de investigación se centra en analizar el liderazgo de las empresas procesadoras de café, bajo la norma ISO 9001:2015. Se tiene como objetivo principal analizar el liderazgo de las empresas procesadoras de café en el cantón Piñas, basado en la norma ISO 9001:2015, con el fin de contribuir al desarrollo socioeconómico de la región. Para ello se emplean métodos de investigación cualitativos y cuantitativos. La recolección de datos se realiza mediante la aplicación de entrevistas dirigidas a gerentes y encuestas a empleados, la población objeto de estudio son las empresas procesadoras de café en la provincia de El Oro cantón Piñas, con un enfoque en dos empresas específicas: Café Don Manuelito y Café Zambrano y se utilizan herramientas de análisis de datos, como el modelo SERVQUAL, que permite evaluar dimensiones claves del liderazgo. Los resultados muestran que los gerentes solo poseen conocimientos sobre el liderazgo y se pretende la aplicación de la norma ISO 9001:2015. Se concluye que el estilo de liderazgo aplicado es mayoritariamente democrático, fomentando así la participación y el compromiso de los empleados. También se determina que el nivel de liderazgo en estas empresas es bueno, según la percepción de los colaboradores. Se espera que los hallazgos de la investigación contribuyan a mejorar el conocimiento sobre la implementación del liderazgo según la norma ISO 9001:2015. Se destaca la importancia de capacitar al personal en liderazgo y trabajo en equipo, así como la elaboración de manuales de funciones para clarificar roles dentro de las empresas.
Keywords: LIDERAZGO; NORMAS ISO 9001:2015; CAFE; EMPRESAS PROCESADORAS